2019
DOI: 10.4103/aer.aer_182_18
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of oral midazolam syrup and intranasal midazolam spray for sedative premedication in pediatric surgeries

Abstract: Introduction: Midazolam is a water-soluble benzodiazepine which is frequently administered by intravenous and oral routes. Its nasal spray has become recently available. Materials and Methods: In this study, after obtaining clearance from the ethical committe, 66 patients between the age group of 4 and 10 years comparable in demographic variables were randomly allocated into two groups of 33 each. Group “O” received oral midazolam (0.5 mg/kg) 20 min before induction. Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Regarding the oral and intraoral routes, in the analysed studies, there were no significant differences among the oral, intraoral (oral mucosa) and intranasal administration of midazolam in terms of the degree of anxiety reduction [8,20,21], the total length of hospital stay [8,20] and the occurrence of adverse effects. This was evidenced in other studies that considered these routes safe and effective for sedation in children [25]. However, several studies showed that the intranasal route presents a faster initiation of action and a better sedation outcome [21,25,26] and better recovery of the child [25,27].…”
Section: Oral and Intraoral Routementioning
confidence: 90%
See 1 more Smart Citation
“…Regarding the oral and intraoral routes, in the analysed studies, there were no significant differences among the oral, intraoral (oral mucosa) and intranasal administration of midazolam in terms of the degree of anxiety reduction [8,20,21], the total length of hospital stay [8,20] and the occurrence of adverse effects. This was evidenced in other studies that considered these routes safe and effective for sedation in children [25]. However, several studies showed that the intranasal route presents a faster initiation of action and a better sedation outcome [21,25,26] and better recovery of the child [25,27].…”
Section: Oral and Intraoral Routementioning
confidence: 90%
“…This was evidenced in other studies that considered these routes safe and effective for sedation in children [25]. However, several studies showed that the intranasal route presents a faster initiation of action and a better sedation outcome [21,25,26] and better recovery of the child [25,27].…”
Section: Oral and Intraoral Routementioning
confidence: 90%
“…6 We did not consider placebo control because the superiority of 0.2mgkg −1 -0.5mgkg −1 midazolam by intranasal route to placebo has already been well established in previous studies. [6][7][8] The children were selected in the age group of 2-6 years, because they have limited scope for psychological counselling. We opined that parental administration of drug would lower the incidence of stranger anxiety during administration and non-compliance, hence was adopted in the methodology of our research.…”
Section: Discussionmentioning
confidence: 99%
“…22 There were no adverse events like hypotension, respiratory depression, nausea and vomiting and delayed recovery from giving midazolam in our study and numerous other studies which makes it the safest drug there is for anxiolysis preoperatively. [6][7][8][9][10][11][12][13] Malinovisky has suggested neurotoxicity in rabbit with intranasal midazolam and ketamine premedication, 26 however recent researches refute the same by affirming that the low pH of the solution is responsible for neurotoxicity only when given epidurally or intrathecally. 27 Morever, many previous studies have used intranasal midazolam without any evidence of nasal mucosa damage or neurotoxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation